Аденилатная система тканей двустворчатого моллюска Anadara inaequivalvis в условиях экспериментальной аноксии - Солдатов, А.А.; Сысоева, И.В.; Сысоев, А.А.; Андреенко, Т.И. (Гидробиологический журнал, 2010)
В экспериментальных условиях изучено влияние аноксии на энергетический статус тканей двустворчатого моллюска Anadara inaequivalvis Br. Аноксия вызывает снижение пула адениловых нуклеотидов и энергетического потенциала тканей в целом. Последнее находит отражение в уменьшении содержания фракций АТФ, АДФ, а также значений аденилатного энергетического заряда (АЭЗ) и фосфорильного потенциала (ФП). При этом величина снижения в условиях 3-суточной аноксии по всем изучаемым показателям не превышает 4045%. Это позволяет предположить, что наблюдаемые изменения состояния аденилатной системы тканей моллюска носят сбалансированный характер и являются функционально достаточными для поддержания суббазальных скоростей метаболизма. В експериментальних умовах вивчено вплив аноксії на енергетичний статус тканин двостулкового молюска Anadara іnaequіvalvіs Br. Тривалість експерименту 3 доби. Температура води утримувалася на рівні 20 ± 1oС, солоність становила 1718, фотоперіод 12 год день : 12 год ніч. Тканини анадари мають низький енергетичний статус, що зумовлює знижений рівень АТФ і невисокі значення аденілатного енергетичного заряду (АЕЗ) і фосфорильного потенціалу (ФП). Це добре корелює зі зниженими кисневими потребами цього виду в умовах нормоксії, що були описані раніше. Загибелі тварин протягом експерименту не спостерігали. Аноксія викликає зниження пулу аденілових нуклеотидів і енергетичного потенціалу тканин у цілому. Останнє знаходить відображення у зменшенні вмісту фракцій АТФ, АДФ, а також значень АЕЗ і ФП. При цьому зниження всіх досліджуваних показник ів в умовах 3-добової аноксії не перевищує 4045%. Це дозволяє припустити, що зміни стану аденілатної системи тканин молюска, що спостерігаються, мають збалансований характер і є функціонально достатніми для підтримки суббазальних швидкостей метаболізму. Influence of an anoxia on the energy status of tissues of bivalvia mollusc Anadara inaequivalvis Br. was investigated under experimental conditions. The experiment exposition was 3 days. The temperature of water was kept up at a level of 20 ± 1oC. Salinity was 17—18‰. The photoperiod—12 hours day : 12 hours night. Initially A. inaequivalvis tissues have the low energy status that shows lowered ÀÒP level and low values of adenylate energy charge (ÀEC) and phosphorylating potential (PhP). It correlates well with the reduced oxygen requirements of this species under normoxia conditions, which have been described earlier. Animal death was not observed during experiment. The anoxia causes decrease of adenylate nucleotides pool and an energy potential of tissues in a whole. The last reveals in reduction of the ATP, ADP contents and also values ÀEC and PhP. Under conditions of 3 days anoxia the value of decrease in all investigated parameters does not exceed 40—45%. It allows to assume, that observed changes of a adenylate system state have balanced character of mollusc tissues and are functionally sufficient for maintenance of metabolism subbasic rate.